Moderasi Beragama dalam Pendekatan Psikologi Sosial - Etikasari (Bahasa Indonesia, 2025)
Religious attitude is a state within a person that encourages them to behave according to their beliefs. Attitude is a predisposition to act positively or negatively, agree or disagree towards a certain object based on psychological components; cognition, affection, and conation. In other words, attitude is the interaction of the complex components of human psyche towards its environment. The purpose of this research is to understand how the behavior of a multicultural society creates religious moderation. This study uses descriptive analysis, resulting in a multicultural society in the city of Medan in terms of development and the impact of religious ethos. Multicultural society shows an environment of civilized, noble, virtuous, egalitarian, and respects individuals based on their work achievements. In addition, a multicultural society upholds the law, tolerance, pluralism, social justice, and brings democracy to life through deliberative forums in the practice of religious moderation.